Age-related differences in motor unit discharge rate modulation across contraction levels - Christopher D. Connelly; Tamara Valenčič; Haydn Thomason; Ed Sadula; Gregory E. P. Pearcey; Mathew Piasecki; Jonathan P. Folland; Jakob Škarabot (GeroScience, 2026)
Age-related strength loss may reflect morphological and neural adaptations that differ between muscles. However, it is unclear how ageing affects motor unit (MU) discharge rate modulation and estimates of persistent inward currents (PICs) across contraction levels. Thirty young (24 ± 4 years) and thirty older adults (73 ± 4 years) underwent magnetic resonance imaging and performed unilateral isometric dorsiflexion and knee extension contractions. Individual MU spike trains were identified from decomposed high-density electromyography recordings of tibialis anterior (TA) and vastus lateralis (VL) during triangular contractions at 30%, 50%, and 70% of maximal voluntary force (MVF). Older adults exhibited lower isometric strength in both tasks and smaller quadriceps but greater shank anterior compartment cross-sectional area compared to young. TA MU discharge rate was lower in older adults at all contraction levels but only at ≤ 50% MVF in VL. Discharge rate hysteresis (∆F), an estimate of PIC contribution to MU discharge, was lower in older adults at all TA contraction levels, but only at 70% MVF in VL, and in both muscles older adults exhibited an attenuated increase in ∆F across contraction levels. The ascending discharge rate non-linearity did not differ between groups, except at 30% MVF in VL where it was greater in older adults. Older adults also exhibited lower acceleration and attenuation slopes in TA, but not VL. These results reveal muscle-specific differences in MU discharge rate modulation with ageing, suggesting that the age-related strength loss is likely underpinned to a greater extent by morphological and neural factors in knee extensors and dorsiflexors, respectively.

Task difficulty and limb dominance modulate the effects of ageing on neuromuscular function - Yuxiao Guo; Eleanor J. Jones; Abdulmajeed Altheyab; Nishadi N. Gamage; Bethan E. Phillips; Philip J. Atherton; Mathew Piasecki (GeroScience, 2026)
Neuromuscular function is critical for independence in ageing, yet asymmetries between dominant and non-dominant limbs, arising from central or peripheral mechanisms, are not well understood. This study examined age- and limb-related differences and motor unit (MU) firing behaviour of the vastus lateralis under tasks of varying difficulty. Twenty-one young (22 ± 4 years; 15 M, 6F) and seventeen older adults (74 ± 5 years; 12 M, 5F) performed constant and variable force unilateral isometric knee extensions. In both limbs, high-density surface electromyography signals were decomposed into MU spike trains. Force control and MU firing properties were analysed using multilevel mixed-effects regression models. Older adults showed reduced maximal muscle strength ( p < 0.001) and increased force tracking error ( p = 0.008). Force outcomes, including muscle strength and force control, showed no significant limb-specific differences in either age group. MU firing rate (MUFR) was significantly lower in older adults during constant contractions ( p = 0.001) and trended toward lower during variable contractions ( p = 0.061). MUFR variability showed a significant Leg × AgeGroup interaction ( p < 0.001); older adults had greater variability in non-dominant legs, while younger adults showed the opposite. With variable force contractions in both age groups, MUFR was higher during ascending segments with greater variability during descending segments. Neuromuscular ageing involves asymmetric adaptations rather than a uniform decline, with leg dominance effects being more pronounced under variable force modulation. Task difficulty amplifies these asymmetries, underscoring the need to consider limb-specific neural control in age-related motor assessments.

Transcranial alternating current stimulation improves ballistic motor performance in trained and untrained limbs of healthy older adults - Nishadi N. Gamage; Wei-Yeh Liao; Philip J. Atherton; Mathew Piasecki; George M. Opie; John G. Semmler (GeroScience, 2025)

Bilateral neuromuscular adaptation to acute unilateral resistance exercise in healthy older adults - Nishadi N. Gamage; Abdulmajeed Altheyab; Yuxiao Guo; Bethan E. Phillips; George M. Opie; John G. Semmler; Philip Atherton; Mathew Piasecki (GeroScience, 2025)
Resistance exercise (RE) enhances functionality in older adults and has proven effective as a means of cross-education in scenarios of unilateral disuse. However, the extent to which older adults demonstrate cross-limb transfer at the motor unit (MU) level following a single bout of unilateral RE is unclear. Thirteen healthy older adults (74.9 ± 4.8 years; 5 females) underwent bilateral neuromuscular assessments pre- and post- a single bout of unilateral RE consisting of sets of 12 repetitions of leg extension of the dominant (exercise) leg, at 75% of 1 repetition maximum, performed to failure. Maximum voluntary contraction (MVC) and force steadiness (FS) were measured. Central and peripheral features of individual MU were recorded using high-density surface electromyography and intramuscular electromyography (HDs/iEMG), during contractions normalised to 25% MVC. Following unilateral RE, MVC reduced in exercise (-14.8%, p < 0.001) and control (-6.9%, p = 0.003) legs, with reduced FS performance in the exercise leg compared to the control (p = 0.002). MU firing rate increased during contractions normalised to 25% baseline MVC in the exercised leg ( p < 0.05), with no adaptation in the control leg ( p > 0.05). All iEMG recorded measures of MU potentials remained unchanged in both legs (all p > 0.05). Acute unilateral RE leads to bilateral MVC reduction in older males and females, demonstrating the cross-limb transfer effect. However, adaptation of MU features was only apparent in the exercised limb, and mechanisms underlying the force decline in the non-exercised limb remain uncertain.

Common synaptic inputs and persistent inward currents of vastus lateralis motor units are reduced in older male adults - Yuxiao Guo; Eleanor J. Jones; Jakob Škarabot; Thomas B. Inns; Bethan E. Phillips; Philip J. Atherton; Mathew Piasecki (GeroScience, 2024)
Although muscle atrophy may partially account for age-related strength decline, it is further influenced by alterations of neural input to muscle. Persistent inward currents (PIC) and the level of common synaptic inputs to motoneurons influence neuromuscular function. However, these have not yet been described in the aged human quadriceps. High-density surface electromyography (HDsEMG) signals were collected from the vastus lateralis of 15 young (mean ± SD, 23 ± 5 y) and 15 older (67 ± 9 y) men during submaximal sustained and 20-s ramped contractions. HDsEMG signals were decomposed to identify individual motor unit discharges, from which PIC amplitude and intramuscular coherence were estimated. Older participants produced significantly lower knee extensor torque ( p < 0.001) and poorer force tracking ability ( p < 0.001) than young. Older participants also had lower PIC amplitude ( p = 0.001) and coherence estimates in the alpha frequency band ( p < 0.001) during ramp contractions when compared to young. Persistent inward currents and common synaptic inputs are lower in the vastus lateralis of older males when compared to young. These data highlight altered neural input to the clinically and functionally important quadriceps, further underpinning age-related loss of function which may occur independently of the loss of muscle mass.

Circulating testosterone and dehydroepiandrosterone are associated with individual motor unit features in untrained and highly active older men - Yuxiao Guo; Jessica Piasecki; Agnieszka Swiecicka; Alex Ireland; Bethan E. Phillips; Philip J. Atherton; Daniel Stashuk; Martin K. Rutter; Jamie S. McPhee; Mathew Piasecki (GeroScience, 2022)
Long-term exercise training has been considered as an effective strategy to counteract age-related hormonal declines and minimise muscle atrophy. However, human data relating circulating hormone levels with motor nerve function are scant. The aims of the study were to explore associations between circulating sex hormone levels and motor unit (MU) characteristics in older men, including masters athletes competing in endurance and power events. Forty-three older men (mean ± SD age: 69.9 ± 4.6 years) were studied based on competitive status. The serum concentrations of dehydroepiandrosterone (DHEA), total testosterone (T) and estradiol were quantified using liquid chromatography mass spectrometry. Intramuscular electromyographic signals were recorded from vastus lateralis (VL) during 25% of maximum voluntary isometric contractions and processed to extract MU firing rate (FR), and motor unit potential (MUP) features. After adjusting for athletic status, MU FR was positively associated with DHEA levels ( p = 0.019). Higher testosterone and estradiol were associated with lower MUP complexity; these relationships remained significant after adjusting for athletic status ( p = 0.006 and p = 0.019, respectively). Circulating DHEA was positively associated with MU firing rate in these older men. Higher testosterone levels were associated with reduced MUP complexity, indicating reduced electrophysiological temporal dispersion, which is related to decreased differences in conduction times along axonal branches and/or MU fibres. Although evident in males only, this work highlights the potential of hormone administration as a therapeutic interventional strategy specifically targeting human motor units in older age.

Lifelong exercise is associated with more homogeneous motor unit potential features across deep and superficial areas of vastus lateralis - Eleanor J. Jones; Jessica Piasecki; Alex Ireland; Daniel W. Stashuk; Philip J. Atherton; Bethan E. Phillips; Jamie S. McPhee; Mathew Piasecki (GeroScience, 2021)
Motor unit (MU) expansion enables rescue of denervated muscle fibres helping to ameliorate age-related muscle atrophy, with evidence to suggest master athletes are more successful at this remodelling. Electrophysiological data has suggested MUs located superficially are larger than those located deeper within young muscle. However, the effects of ageing and exercise on MU heterogeneity across deep and superficial aspects of vastus lateralis (VL) remain unclear. Intramuscular electromyography was used to record individual MU potentials (MUPs) and near fibre MUPs (NFMs) from deep and superficial regions of the VL during 25% maximum voluntary contractions, in 83 males (15 young (Y), 17 young athletes (YA), 22 old (O) and 29 master athletes (MA)). MUP size and complexity were assessed using area and number of turns, respectively. Multilevel mixed effects linear regression models were performed to investigate the effects of depth in each group. MUP area was greater in deep compared with superficial MUs in Y ( p <0.001) and O ( p =0.012) but not in YA ( p =0.071) or MA ( p =0.653). MUP amplitude and NF MUP area were greater, and MUPs were more complex in deep MUPs from Y, YA and O (all p <0.05) but did not differ across depth in MA (all p >0.07). These data suggest MU characteristics differ according to depth within the VL which may be influenced by both ageing and exercise. A more homogenous distribution of MUP size and complexity across muscle depths in older athletes may be a result of a greater degree of age-related MU adaptations.

Measurement of muscle health in aging - Peter Francis; Mark Lyons; Mathew Piasecki; Jamie Mc Phee; Karen Hind; Philip Jakeman (Biogerontology, 2017)

Age-dependent motor unit remodelling in human limb muscles - Mathew Piasecki; Alex Ireland; David A. Jones; Jamie S. McPhee (Biogerontology, 2016)